Effect of equilibration period on quality of frozen semen in Beetal x Assam local crossbred goats - BARUAH, C K; BISWAS, R K; DEKA, B C; BORGOHAIN, B N (The Indian Journal of Animal Reproduction, 2003)
A total of 36 pooled ejaculates collected from four adult crossbred goats (Beetal x Assam Localgoats) were used to study the effect of three equilibration periods on quality of frozen semen. Thesemen extended in Tris-egg yolk-citric acid-fructose-glycerol extender was frozen in French mediumstraws in liquid nitrogen vapour. The mean per cent sperm motility and intact sperm acrosome afterfreezing were significantly higher at 5 hours (54.58±1.30, 81.33±0.17) than at 3 (48.75±1.39, 80.58±0.25)and 7 (51.67±0.71, 79.21±0.31) hours of equilibration periods.
Keywords: Equilibration period; frozen semen, sperm motility; intact acrosome; crossbred goat